The Effect of Implementing Self-Compassion Program on Moral Injury of Nursing Students - Hanie Dahmardeh (Archives of Anesthesia and Critical Care)
Background: Self-compassion can have a significant role and impact on moral damage, and the positive components of self-compassion (self-kindness, common human sense, and mindfulness) reduce the negative effects of moral damage, so using self-compassion methods can reduce the moral damage caused to nursing students during their studies. Therefore, the present study was conducted with the aim of determining the effect of the self-compassion program on the moral damage of nursing students in 2024. Methods: In this clinical trial study, 150 nursing students of the 7th and 8th semesters in the intership course of Zahedan School of Nursing in 2023 were randomly selected in two groups of 75, intervention and control. 8 sessions of face-to-face educational program were designed and implemented for students and the degree of application of the programs by them was followed up under the supervision of the researcher. Before and 2 months after the implementation of the intervention, students' moral damage was measured using the moral damage questionnaire. Data were analyzed using independent t, paired t and chi square statistical tests under SPSS 21 statistical software. Results: The results showed a statistically significant difference for the average score of moral injury between the control and intervention groups (P=0.001). On the other hand, the t-pair test shows a significant increase in the mean score of moral injury two months after the completion of the educational intervention in the intervention group (P=0.001). Conclusion: The results of the present study showed that the current self-compassion training program can reduce the moral damage of nursing students during the 7th and 8th semesters, before entering the hospital as a professional nurse; Therefore, it is necessary to use it in future planning for nursing students during the 7th and 8th semester.